2018
DOI: 10.1097/gox.0000000000001928
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and Systematic Review of Skin Graft Donor-site Dressings with Future Guidelines

Abstract: Background:Many types of split-thickness skin graft (STSG) donor-site dressings are available with little consensus from the literature on the optimal dressing type. The purpose of this systematic review was to analyze the most recent outcomes regarding moist and nonmoist dressings for STSG donor sites.Methods:A comprehensive systematic review was conducted across PubMed/MEDLINE, EMBASE, and Cochrane Library databases to search for comparative studies evaluating different STSG donor-site dressings in adult sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…In other words, there seems to be a worse agreement in the judgment of donor-site scars compared to the recipient site. [26][27][28][29] Caregivers should be aware of these options, which may increase scar quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, there seems to be a worse agreement in the judgment of donor-site scars compared to the recipient site. [26][27][28][29] Caregivers should be aware of these options, which may increase scar quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies on the outcomes of these treatment options focus on early and rapid re-epithelialization but lack data on patient reported (long term) scar appearance. 26 Further research is, therefore, necessary to investigate which patients benefit from these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In this thesis, we focus on donor sites created when the surgeon harvests split thickness skin grafts. In Study I, skin grafts are harvested from the thigh with the dermatome (skin harvesting "machine") set to 0.012 inches, which produces medium/intermediate thick grafts, and creates a wound approximately 0.2 -0.3 mm deep This should leave the epidermal appendages (glands and follicles) of the dermis almost intact [29,30]. The most commonly-used donor site is the thigh [30].…”
Section: Description Of the Wound Models Of This Thesismentioning
confidence: 99%
“…Closed moist dressings are further claimed to lower the risk of contamination from the surroundings [63]. Five systematic reviews on donor site dressings were found and in four of them the authors conclude that a moist wound environment is associated with better outcomes, as in faster re-epithelialisation, less pain, and fewer infections [30,[64][65][66][67].…”
Section: Dressing Treatmentsmentioning
confidence: 99%
“…Unfortunately, if an alginate or hydrofiber dressing is left in situ throughout healing, the dressing is likely to dry out and possibly adhere to the wound bed [3]. Furthermore, two systematic reviews of donor-site dressing found no clear evidence to support the choice of any particular dressing [4, 5] except that they must be moist; occlusive or semi-occlusive dressings both fall into this category.…”
Section: Introductionmentioning
confidence: 99%